Appreciating the political ethnography of master narratives and counterstories - Moore, Philip (Springer, 2011)
Here I write an appreciation of Settlage’s account of experiences with pre-service teachers in the United States. Focusing on his use of notions of narrative and counterstories I explore the politics of experience in education looking at how he uses narrative and story, the politics entailed in the polyvocal evidence he presents and the significance of the ethnographic context for his account. After a discussion of these three significant conceptual insights I conclude with a return to his account and his somewhat diffident reflections about the project he reports on.